INVESTIGATING IMPACT OF BILLET THICKNESS ON HAMMER OPERATION QUALITY - Viktor I. Mirny (Advanced Engineering Research, 2012)
The numerical analysis results for the impact of the billet thickness of some steel qualities on the operating speed and efficiency of the hammer are presented.